LUX ARRHYTHMO mediates crosstalk between the circadian clock and defense in Arabidopsis - Chong Zhang (Nature Portfolio, 2019)
Circadian control of plant defence likely reflects plants’ ability to coordinate development and defense. Here, Zhang et al. show that LUX regulates stomatal defense  and SA/JA signaling, leading to broad-spectrum disease resistance, and that JA signaling can, in turn, regulate clock activity.